2020
DOI: 10.1155/2020/7254972
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining, Forming, and Letting Go of Friendships for Young People with Inflammatory Bowel Disease (IBD): A Qualitative Interview-Based Study

Abstract: Inflammatory bowel disease (IBD) is an incurable, chronic, gastrointestinal condition that can constrain young people’s social relationships. Few studies have specifically explored friendships of people with IBD. This qualitative, participatory study used interviews, photographs, and friendship maps to explore friendships and friendship networks of young people with IBD. An online Young Person’s Advisory Group was actively engaged throughout the study. Thirty-one young people participated (n=16 males, n=15 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…A recent qualitative study ( 54 ) suggested that openness about IBD with friends can be a PPFP for young people, theoretically by facilitating increased opportunities for meaningful, supportive friendships. An additional study found that friendships were seen as important by young people with IBD, specifically in the sense that friends facilitated maintaining a sense of normalcy and provided understanding, which felt particularly supportive during disease exacerbation ( 72 ). While not directly assessing peer support, studies examining summer camps for youth with IBD (e.g., Camp Oasis, Camp Gut Busters) found that the majority of respondents indicated camp, which inherently was centered around engaging with other youth with IBD, was associated with desired outcomes such as increased HRQoL ( 73 , 74 ), improved confidence, increased disease-related self-efficacy, increased sense of belonging, and increased social connection ( 75 - 77 ).…”
Section: Dimension 2: Ppfpsmentioning
confidence: 99%
“…A recent qualitative study ( 54 ) suggested that openness about IBD with friends can be a PPFP for young people, theoretically by facilitating increased opportunities for meaningful, supportive friendships. An additional study found that friendships were seen as important by young people with IBD, specifically in the sense that friends facilitated maintaining a sense of normalcy and provided understanding, which felt particularly supportive during disease exacerbation ( 72 ). While not directly assessing peer support, studies examining summer camps for youth with IBD (e.g., Camp Oasis, Camp Gut Busters) found that the majority of respondents indicated camp, which inherently was centered around engaging with other youth with IBD, was associated with desired outcomes such as increased HRQoL ( 73 , 74 ), improved confidence, increased disease-related self-efficacy, increased sense of belonging, and increased social connection ( 75 - 77 ).…”
Section: Dimension 2: Ppfpsmentioning
confidence: 99%
“…Individuals with IBD experience potential challenges to their psychological well-being: the course of the disease is unpredictable, the treatment and management regimes frustrating. Patients talk about the symptoms of the disease often being embarrassing and socially limiting [ 3 , 11 ], which makes telling others about their condition difficult [ 12 , 13 ]. While there are few studies with adolescents and young adults (AYA) with IBD, those studies show high rates of anxiety and depression among that population [ 14 ].…”
Section: Ibd and Mental Healthmentioning
confidence: 99%
“…Fears of abdominal pain, bowel noises, faecal incontinence, and/or a bowel urgency in public mean many people with IBD withdraw from social interactions because they feel ashamed. IBD nondisclosure due to embarrassment is also a reported problem in the literature [ 13 , 26 ], but, because concealment of any condition is associated with reduced engagement with others [ 28 ], feelings of disconnection and negative affect are likely to be high among those with IBD because of social problems as much as they are to do with disease severity. Indeed, recent work by Roberts, Gamwell et al [ 29 ] showed that difficulty communicating about their illness to others was associated with thwarted belonging that was also linked to higher depression.…”
Section: Risk Factors For Poor Mental Health Among Aya With Ibdmentioning
confidence: 99%
“…However, there is another period in a person’s life of great importance in the development of routines and behavioral habits that will later affect the health and well-being of the individual, and that is the period of youth. This period coincides with significant changes: leaving the family home to live more independently ( 5 ), a change of schedule that in many cases leads to a reduction in physical activity ( 6 ) or the creation of new friendships and, with it, often new fun routines ( 7 ).…”
Section: Introductionmentioning
confidence: 99%